2013
DOI: 10.1371/journal.pone.0069683
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Conflict Control on Facial Expressions with A Flanker Paradigm

Abstract: Conflict control is an important cognitive control ability and it is also crucial for human beings to execute conflict control on affective information. To address the neural correlates of cognitive control on affective conflicts, the present study recorded event-related potentials (ERPs) during a revised Eriksen Flanker Task. Participants were required to indicate the valence of the central target expression while ignoring the flanker expressions in the affective congruent condition, affective incongruent con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…In line with prior studies, it was currently observed that the response speed was faster to identify happy faces than fearful faces (Leppänen et al, 2003 ; Leppänen and Hietanen, 2004 ; Schulz et al, 2007 ). In addition, participants performed with higher accuracies when identifying happy faces in congruent trials (HHHHH) than in incongruent trials (FFHFF), which was consistent with previous findings of conflict control on emotional information (Eastwood et al, 2001 ; Fenske and Eastwood, 2003 ; Rowe et al, 2007 ; Ochsner et al, 2009 ; Liu et al, 2013 ). Fenske and Eastwood’s ( 2003 ) behavioral findings manifested that the flanker-compatibility effect was smaller for negative target faces compared with positive target faces, which illustrated that the constriction of attention could be influenced by the valence of emotional faces.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with prior studies, it was currently observed that the response speed was faster to identify happy faces than fearful faces (Leppänen et al, 2003 ; Leppänen and Hietanen, 2004 ; Schulz et al, 2007 ). In addition, participants performed with higher accuracies when identifying happy faces in congruent trials (HHHHH) than in incongruent trials (FFHFF), which was consistent with previous findings of conflict control on emotional information (Eastwood et al, 2001 ; Fenske and Eastwood, 2003 ; Rowe et al, 2007 ; Ochsner et al, 2009 ; Liu et al, 2013 ). Fenske and Eastwood’s ( 2003 ) behavioral findings manifested that the flanker-compatibility effect was smaller for negative target faces compared with positive target faces, which illustrated that the constriction of attention could be influenced by the valence of emotional faces.…”
Section: Discussionsupporting
confidence: 89%
“…The P3 responses are associated with conflict resolution and allocation of attentional control (Hillman et al, 2009a , b ; Clayson and Larson, 2011 ), and the incongruent trials induce larger P3 than the congruent trials (Hillman et al, 2009a , b ). Previous behavioral and electrophysiological studies showed that response speed was faster in emotional congruent trials than emotional incongruent trials, and happy faces with sad distracters induced more negative N2 amplitudes than happy faces flanked by identical faces during conflict monitoring stage (Fenske and Eastwood, 2003 ; Liu et al, 2013 ); while during the conflict resolution stage, happy faces in the incongruent trials elicited slower P3 responses compared to that in the congruent trials, and the attentional control on sad faces in the incongruent trials induced larger P3 responses than that in the congruent trials (Fenske and Eastwood, 2003 ; Liu et al, 2013 ). In the same line, Ochsner et al ( 2009 ) adopted functional magnetic resonance imaging (fMRI) technology to investigated conflict control on affective words and reported that bilateral dorsal ACC were strongly activated in the affective incongruent condition.…”
Section: Introductionmentioning
confidence: 97%
“…Additional research in anxious patients is needed to test whether cognitive control perturbations in anxiety vary as a function of the emotional versus nonemotional sources of conflict. Paradigms such as the face-word Stroop task (Etkin et al 2006;Egner et al 2008) and the Eriksen flanker task (Ochsner et al 2009;Alguacil et al 2013;Liu et al 2013) have been studied using matched-task versions that compare emotional versus nonemotional forms of cognitive control, and are, therefore, well suited to test this hypothesis. Attempts to replicate anxietyrelated differences in cognitive control should simultaneously examine measures of conflict adaptation, post-error slowing/accuracy, and ERN, to explore how robust the phenomena are and, whenever possible, directly compare emotional and nonemotional tasks to test for affect-based specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The facial images in the revised emotional flanker task (Fenske and Eastwood, 2003;Liu et al, 2013) were of the face of six models (three males, three females) displaying both happy and fearful faces. The face stimuli were from our lab's collection, and they were collected and used under the standardized procedure.…”
Section: Emotional Flanker Taskmentioning
confidence: 99%
“…According to the dimensional overlap theory (Kornblum et al, 1990(Kornblum et al, , 1999, conflicts can be further categorized based on the overlap between the response (R), the taskrelevant stimulus (SR), and the task-irrelevant stimulus (SI). The emotional flanker task contains the stimulus-stimulus (S-S) conflicts that SR (the target emotional facial expression) overlaps with SI (the bilateral distractor emotional faces) (Fenske and Eastwood, 2003;Liu et al, 2013). The emotional Stroop task contains both S-S and S-R conflicts, with the affective word ("FEARFUL" or "HAPPY") on an emotional (happy or fearful) face, and participants are required to report the expression on the face (Etkin et al, 2006(Etkin et al, , 2010Egner, 2008;Liu et al, 2010;Chechko et al, 2012;Soutschek and Schubert, 2013).…”
Section: Introductionmentioning
confidence: 99%